Identificación de factores de siniestrabilidad laboral de una - Medina, Juan (2010)
The present work has like aim, identify the possible factors of siniestrabilidad labour, in a company devoted to the production of electrical teams, and know if said factors identified influence in the occurrence and degree of dangerousness of the labour accident, splitting of the study of the causes that generate accidents in the installations and areas of work where carries out the production of said teams. The correct execution of a project of this magnitude, depends to a large extent of the management realized, scheduling the activities of field, defining all and each one of the tasks to effect before, during and after the production; organizing the available resources, and especially under an excellent direction, control and monitored of the project. Always optimizing the costs of production; the direct costs of hand of work; the expense in teams and material; and the indirect costs of administration; and general